ChemInform Abstract: Synthetic Potassium Vanadium Oxide K2V6O16·1.5H2O Superlong Nanobelts: A 1D Room‐Temperature Ferromagnetic Semiconductor. Issue 49 (3rd December 2013) - Bai, Liangfei; Xue, Yan; Zhang, Jiajia; Pan, Bicai; Wu, Changzheng
Abstract K2V6O16·1.5H2O superlong nanobelts are hydrothermally synthesized from aqueous solutions of K3VO4 and HCl (autoclave, pH 3, 200 °C, 24 h) and characterized by powder XRD, SEM, TEM, XPS, and magnetic and electrical measurements.